Elevation of C-reactive protein and homocysteine levels as reliable biomarkers for assessing injury severity and prognosis in traumatic brain injury - Zi-Yan Wang; Wei Du; Xian-Zhi Liu; Yuan Li; Jun Liu (Scientific Reports)
Abstract This study evaluated the clinical utility of C-reactive protein (CRP) and homocysteine (Hcy) as biomarkers for injury severity assessment and prognostic prediction in traumatic brain injury (TBI). A retrospective cohort study included 103 TBI patients (February 2020 to February 2023) stratified by Glasgow Coma Scale (GCS) scores into mild (n = 20), moderate (n = 32), and severe (n = 51) injury groups, alongside 20 healthy controls. Serum and cerebrospinal fluid (CSF) CRP and Hcy levels were measured serially over 14 days post-injury. Prognostic outcomes were assessed using 3-month Glasgow Outcome Scale (GOS) and modified Rankin Scale (mRS) scores. Severe TBI patients exhibited significantly higher serum and CSF CRP levels than moderate/mild groups (p < 0.01), peaking within 72 h and remaining elevated through day 14. Serum Hcy levels increased rapidly post-injury, with severe cases sustaining prolonged elevations (> 7 days vs. ≤3 days in mild/moderate groups). CRP and Hcy levels inversely correlated with admission GCS scores (r = − 0.756, 0.756 and − 0.652, respectively; p < 0.001) and positively correlated with intracranial pressure (r = 0.829, 0.779 and 0.633). The initial CRP and Hcy levels were negatively correlated with GOS and positively correlated with mRS at 3 months post-injury, indicating their potential as biomarkers for assessing injury severity and predicting prognosis in TBI patients. CRP (serum/CSF) and serum Hcy are reliable biomarkers for assessing injury severity and predicting prognosis in TBI patients.